Oil Processes VR Training - Andaluz, Víctor H.; Amaquiña, José L.; Quevedo, Washington X.; Mora-Aguilar, Jorge; Castillo-Carrión, Daniel; Miranda, Roberto J.; Pérez, María G. (Advances in Visual Computing, 2018)
In this paper a virtual reality solution is developed to emulate the environment and the operations of the pitching and receiving traps of pipe scrapers (PIG), with the aim of reinforcing the training of operators in oil camps. To develop this, the information was collected on various pitching and receiving traps of the real pipeline operating companies in the country, thus defining the basic and specific parameters for the virtual recreation of a typical trap model. The 3d models obtains from P&ID’s diagrams to interact with user. The environment, interaction and behavior of pipes was developed in a graphic engine, to make training tasks with real state procedures on the oil industry. The goal is save time, money, resources in the training and learning specific oil industry; and make available a base to simulate another complex process.